Design of a system to detect diseased spots on fishes - Sarker, Rakesh; Gulshanra, Zainab; Zahin, Abrar; Chowdhury, Emon (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.